Learning who to trust: policy learning in single-stage decision problems with unreliable expert advice - Love, Tamlin (My University, 2022)
Work in the field of Assisted Reinforcement Learning (ARL) has shown that the incorporation of external information in problem solving can greatly increase the rate at which learners can converge to an optimal policy and aid in scaling algorithms to larger, more complex problems. However, these approaches rely on a single, reliable source of information; the problem of learning with information from multiple and/or unreliable sources of information is still an open question in ARL. We present CLUE (Cautiously Learning with Unreliable Experts), a framework for learning single-stage decision problems with policy advice from multiple, potentially unreliable experts. We compare CLUE against an unassisted agent and an agent that naiıvely follows advice, and our results show that CLUE exhibits faster convergence than an unassisted agent when advised by reliable experts, but is nevertheless robust against incorrect advicef rom unreliable experts.
A research report submitted to the School of Computer Science and Applied Mathematics, Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree Master of Science, 2022